2018
DOI: 10.1051/limn/2018026
|View full text |Cite
|
Sign up to set email alerts
|

Mollusc fisheries and length–weight relationship in Tonle Sap flood pulse system, Cambodia

Abstract: Molluscs are important for ecological function, livelihoods and fisheries, but are often forgotten in research and management. Here, we investigated intra-annual variation in the landing and growth patterns of three mollusc species, i.e., Corbicula moreletiana, Pila virescens and Pila ampullacea, using one-year daily data on landing catches and values, recorded in Kampong Chhnang province of Tonle Sap (TS) Lake. Overall, 8330 tonnes with a first sale landing value of US$ 1.4 million for the three species were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Pila gracilis seemed to be rare in the eastern Thai provinces that border Cambodia (Ng et al in press) but appears to be common in the Tonle Sap basin. Although Pila gracilis was not previously recorded as being harvested from the Tonle Sap Lake (Ngor et al 2016(Ngor et al , 2018d, we recorded Pila gracilis being sold together with Pila pesmei (Morlet, 1889) and Pila virescens (Deshayes, 1824) at one landing site in Kampong Chhnang Province, and collected Pila gracilis and Pila virescens from within the Lake.…”
Section: Scabies Mandarinus (Morelet 1864) Fig 3kmentioning
confidence: 75%
See 3 more Smart Citations
“…Pila gracilis seemed to be rare in the eastern Thai provinces that border Cambodia (Ng et al in press) but appears to be common in the Tonle Sap basin. Although Pila gracilis was not previously recorded as being harvested from the Tonle Sap Lake (Ngor et al 2016(Ngor et al , 2018d, we recorded Pila gracilis being sold together with Pila pesmei (Morlet, 1889) and Pila virescens (Deshayes, 1824) at one landing site in Kampong Chhnang Province, and collected Pila gracilis and Pila virescens from within the Lake.…”
Section: Scabies Mandarinus (Morelet 1864) Fig 3kmentioning
confidence: 75%
“…4D), and is often sold in markets and roadside stalls. An annual harvest of more than 1500 tonnes of the species was recorded from five commercial landing points in Kampong Chhnang Province (Ngor et al 2018d).…”
Section: Pila Virescens (Deshayes 1824) Fig 5cmentioning
confidence: 99%
See 2 more Smart Citations
“…areas are in fact conditioned by different variables, which can be abiotic (environmental) or biotic (physiological) (Gaspar et al 2002), although in the present study these variables were not taken into account. Growth patterns also vary considering different life stages (Gaspar et al 2002) and seem to vary even within the year, as demonstrated by different b values in monthly length-weight relationships (Tirado & Salas 1998;Ngor et al 2018). Between the North Adriatic and the Central Tyrrhenian Sea, a possible hypothesis explaining this difference may be related to latitude (Beukema & Meehan 1985), depth, type of bottom (Claxton et al 1998) and/or type of sediment (Newell & Hidu 1982).…”
Section: Discussionmentioning
confidence: 99%